The effect of frozen storage on lipids and fatty acids content in Atlantic salmon. Case study - Nicolae, Carmen Georgeta; Bahaciu, Gratziela Victoria; Ţeca, M.; Badulescu, Liliana; Pogurschi, Elena; Marin, Monica (2017)
Being a species appreciated in all parts of the world, the demand for salmon will always be high. Keeping frozen in the entire period of distribution and handling is a way to increase "shelf life". During cold storage, fish fat can be altered. The purpose of the paper is to determine the effect of cold preservation on the quality of salmon fat. These were evidenced by laboratory tests and by gas chromatography and mass spectrometry. It was analysed the samples of refrigerated and frozen fish (preserved at -20ºC, five days) from the same batch. The amount of determined lipids confirms the literature data (26%), respectively 24.99% in the fresh fish and 27.23% in the frozen fish. In frozen fish the amount of oleic acid (MUFA) extracted is higher, to the detriment of linoleic acid (PUFA). The same trend was observed for the amount of saturated fatty acids (SFA), monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA). Most fatty acids of frozen fish were monounsaturated fatty acids (43.99%), followed by polyunsaturated fatty acids (38.74%) and saturated fatty acids (19.56%). These data highlight that frozen fish, even for a short period of time (5 days), alters the content of essential fatty acids, especially polyunsaturated fatty acids.